Antibiotic Utilization and Patient with Sepsis Characteristics: A Multicenter Retrospective Study in Semarang - Gilang Rizki Al Farizi; Tunik Saptawati; Yovita Dwi Arini; Rizky Budi Santoso; Suci Arsita Sari; Lutfi Defita Sari (Universitas Wahid Hasyim Semarang, 2026)
Sepsis remains a critical global health challenge requiring prompt and appropriate antimicrobial intervention to reduce mortality. Despite established guidelines recommending early broad-spectrum antibiotic administration, empirical prescribing patterns and their alignment with clinical recommendations remain insufficiently documented in Indonesian multicenter settings, particularly in Central Java. This study addresses the knowledge gap by evaluating antibiotic utilization profiles and patient characteristics among hospitalized sepsis cases in Semarang, with emphasis on empirical therapy practices and stewardship implications. A multicenter retrospective observational study was conducted involving 200 sepsis patients meeting predefined inclusion criteria from two hospitals in Semarang during 2019–2023. Data were extracted from medical records and analyzed descriptively, considering inter-hospital variability in prescribing practices. Results demonstrated male predominance (51.5%), elderly population representation (42.5% aged >60 years), multiple comorbidity burden (50.5% with two comorbidities), and moderate hospitalization duration (36% for 3–7 days). Broad-spectrum agents active against both Gram-positive and Gram-negative organisms dominated prescribing patterns (89.4%), while time-dependent antibiotics represented 10.5% of prescriptions. Meropenem emerged as the most frequently prescribed agent (33.3%), administered exclusively via the intravenous route (100%). These findings underscore the importance of structured antimicrobial management and robust de-escalation strategies in local hospital settings to effectively balance necessary empirical coverage with the prevention of antimicrobial resistance